Esperanza y atributos de los colaboradores - Rodrigo Arturo Zárate Torres; Julio César Acosta-Prado (Suma de Negocios, 2015)
The relationship between hope and attributes of employees is analysed on a sample of 323 individuals. On the one hand, hope is a construct of positive psychology that was introduced at organisational level during the 1990's. Moreover, the attributes of collaborators has helped to determine and improve skills and, in turn, obtain a better performance in the organisations. The analysis of the data was performed using factorial analysis and correlations between the constructs and the demographic variables, age and gender. The results show that there is a positive and significant relationship between the areas of hope and the attributes of the collaborators about performance.